Making schools practical: Practice firms and their function in the full-time vocational school system in Germany - Deissinger, Thomas [Verfasser] (My University, 2007)
The purpose of this article is to provide information and insight into the potential of reforms in full-time vocational education and training (VET) (practice firms in vocational colleges) in contrast with apprenticeships against the background of training market frictions in Germany. It underlines that vocational colleges and practice firms within them are part of a "preparatory" system which predominantly serves further education needs and the follow-up intention to undertake an apprenticeship. The findings are based on an empirical study (2006) within a research project to illustrate the didactical and social benefits of practice firms. (Autorenreferat, BIBB-Doku)
Keywords: S 1.3.3 Vollzeitschulische Berufsausbildung; L 2 Lehr-Lerngestaltung; I 2.1.2.4 Baden-Württemberg; Schulische Berufsausbildung; Vollzeitschule; Kaufmännische Ausbildung; Berufskolleg; Übungsfirma; Baden-Württemberg